2018
DOI: 10.3892/ijo.2018.4522
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA CASC2 inhibits breast cancer cell growth and metastasis through the regulation of the miR-96-5p/SYVN1 pathway

Abstract: Cancer susceptibility candidate 2 (CASC2), a long non-coding RNA (lncRNA), has been demonstrated to be a tumor suppressor in several types of cancer. However, the role and mechanism of CASC2 in breast cancer (BC) have not been investigated. In the present study, the expression and functions of CASC2 in BC were investigated. The expression of CASC2 was significantly decreased in BC tissues and cells compared with adjacent normal tissues and mammary epithelial cells, respectively. CASC2 overexpression inhibited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 29 publications
(46 reference statements)
0
23
0
Order By: Relevance
“…[ 36 ] CASC2 inhibited breast cancer cell growth and metastasis through the regulation of the miR‐96‐5p/SYVN1 pathway. [ 37 ] Upregulation of CASC2 sensitized glioma to temozolomide cytotoxicity through autophagy inhibition by sponging miR‐193a‐5p and regulating mTOR expression. [ 38 ] Especially, CASC2 upregulated PTEN to suppress proliferation and metastasis of pancreatic cancer cells by downregulating miR‐21 and Akt signaling.…”
Section: Discussionmentioning
confidence: 99%
“…[ 36 ] CASC2 inhibited breast cancer cell growth and metastasis through the regulation of the miR‐96‐5p/SYVN1 pathway. [ 37 ] Upregulation of CASC2 sensitized glioma to temozolomide cytotoxicity through autophagy inhibition by sponging miR‐193a‐5p and regulating mTOR expression. [ 38 ] Especially, CASC2 upregulated PTEN to suppress proliferation and metastasis of pancreatic cancer cells by downregulating miR‐21 and Akt signaling.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, HRD1 inhibited aerobic glycolysis in breast cancer cells, providing new evidence for a role as a regulator of tumor metabolism. Our previous studies had revealed that HRD1 had a tumor suppressive effect that involved suppression of breast cancer cell proliferation, migration and invasion [17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…Induction of ER stress leads to upregulation of several genes such as WARS (tryptophanyl-tRNA synthetase), HERP (homocysteine-inducible ER protein with ubiquitin like domain 1), DNAJC3 (also called P58IPK), ER degradation-enhancing alpha-mannosidase-like 1 (EDEM1) and leads to caspase activation, release of mitochondrial intermembrane proteins and dissipation of mitochondrial transmembrane potential (ΔΨm) [53]. Synovial apoptosis inhibitor 1 (SYVN1), an ER-associated degradation (ERAD) E3 ubiquitin ligase, could inhibit the breast cancer cell growth and metastasis through the miR-96-5p/SYVN1 axis [54]. Site 1 protease (S1P), SREBP cleavage-activating protein (SCAP) and acetyl-CoA acetyltransferase 1 (ACAT1) were involved in the lipid metabolism [55].…”
Section: Discussionmentioning
confidence: 99%